Os sentidos de trabalho para jovens estudantes do ensino médio da cidade de Carapicuíba - Bonfim, Poliana da Paz (2011)
The present study has how I aim to understand the senses of the work for young students of the city of Carapicuíba. The relevance of the subject expands to the discussion on the social unequality and education in the collective and individual extent, while bringing the period of development of the capacities of autonomy and freedom to be stimulated in the school environment, however, before the condition of young persons of low income subjected to the work is limited and substituted by other experiences out of the school. For such an objective, this study took the Psychology as a reference Partner Historical and, from her, the categories of sense: adolescence, work and the dialectic process of exclusion and social inclusion. Interviews were carried out with young students of the Secondary education of state, what public schools they were analysed from the theory of Vigotski. During the analysis, there were identified categories that revealed several forms of demonstration of the perverse inclusion and of the devaluation of the education that appear in the speeches of the young persons and in the routine of the schools, since this one is harmless, it does not affect them, but for the physical tiredness. His positivity is in the possibility while making friends and reaching the university and the work it is seen as the only possibility of pleasure linked to the consumption